TEACHER AND STUDENTS' PERCEPTION ON THE IMPLEMENTATION OF MERDEKA CURRICULUM IN TEACHING ENGLISH - Nur Octaviana; Arif, Abdul; Syahadati, Elly (Journal of English Language Teaching and Education (JELTE), 2025)
Teacher and Students’ Perception on the Implementation of Merdeka Curriculum in Teaching English. This study aimed to explore English teacher’s perceived impacts of Merdeka Curriculum in teaching practice and students’ responses on English teacher teaching practice using Merdeka Curriculum at SMPN 1 Sukadana. The research employed a Concurrent Triangulation Mixed Methods design, collecting quantitative data through a closed-ended questionnaire from 180 eighth-grade students and qualitative data through semi-structured interviews with an experienced English teacher. The findings revealed that the teacher experienced positive impacts such as greater teaching methodology adjustment selection, curriculum context alignment and formative, relevant assessment. This flexibility allowed the teacher to better address the diverse needs of students in a rural setting and improved instructional quality. Students demonstrated positive responses in terms of instructional clarity, classroom atmosphere, learning engagement, teaching effectiveness, and learning independence. The Merdeka Curriculum facilitated adaptive, student-centered, and contextually relevant teaching practices.